Promotional Strategies of Cellular Services : A Customer Perspective - Chinnadurai, M.; Kalpana, B. (Indian Journal of Marketing, 2006)
Major driver of social changes, which shapes the possibilities and conduct of business, is technology. Every business whether it is manufacturing or service faces large amount of problems in marketing their products in the modern business world today. Due to change in the economic, business, cultural and political environment, the consumers resort to have change in their preferences. These changes on the part of consumers may provide either positive or negative impact on the business of modern firms. Accordingly, these firms have to make their business plans more comprehensive and effective. Obviously, the business firms have to sue adequate and appropriate promotional tools for establishment and promotion of their business without more interruptions.